Transformation of Waste Plastic Bottles into Covered Parking - Tantiyaswasdikul, Kallaya (Journal of Architectural/Planning Research and Studies (JARS), 2018)
One of the environmental problems that we have witnessed nowadays comes from the increased volume of garbage. Each year, Thailand generates up to 13.9 million tons of waste which includes plastic packaging and waste material that have a potential to be reused roughly 6 million tons but there is only 2 million tons or 14.4 percent of such reuseable waste being reused. The solution of recycling and reuse could be an alternative approach to create or increase the value of wasted material. Under these circumstances, this research aims at exploring the ways to transform plastic water bottle waste into architectural elements, specifically a roof of covered parking. The prototype was created based on the morphology theory. The result of this design was generated and evaluated with 3D Studio Max program, a computer program that can simulate materials and lighting conditions. The outcomes of this study indicate that the prototype could reduce an amount of radiation penetration with the same level as a light filter, but there are two concerning points which are the maintenance and the cost of the prototype. However, this research could be an example of the architecture that addresses the environmental degradation.